The prevalence of obesity in children and young people with Down syndrome. Issue 6 (15th May 2018) - O' Shea, Muireann; O' Shea, Carol; Gibson, Louise; Leo, Jennifer; Carty, Catherine
Abstract : Background: Overweight and obesity is a growing concern among individuals with intellectual disabilities; however, little is known about the prevalence among children and youth with Down syndrome (CYDS). The purpose of this study was to determine the prevalence of overweight/obesity among CYDS in South West Ireland. Methods: This cross‐sectional study measured height and weight of 61 CYDS aged 4–16 years. Body mass index (BMI) was calculated and percentage body fat (PBF) was measured using bio‐electrical impendence analysis (BIA). Results: Using the International Obesity Task Force BMI cut‐offs, 51.6% of males and 40% of females were overweight/obese compared to 32% and 14.8%, respectively, using PBF. The mean PBF for males was 18.76 versus females 22.38 ( p  < .05). There is a higher prevalence of overweight/obesity, particularly in males, compared to the general population of children. Conclusions: The difference in estimation of overweight/obesity between BMI and BIA has implications for research and clinical practice.